The interweaving of rituals : funerals in the cultural exchange between China and Europe - Standaert, N. (China Program book., 2008)
Demonstrates the interweaving of Chinese and European ritual practices at different levels of interaction in seventeenth-century China. This book explores the role of rituals - specifically rites related to death and funerals - in cross-cultural exchange.